Analisis Pengkhianatan Kreatif dalam Puisi Terjemahan “The Wild Swans at Coole” Karya William Butler Yeats - Prihantono, Kahar Dwi (Kementerian Sekretariat Negara Republik Indonesia, 2019)
The treason in literary translation refers to translator’s subjective efforts to perform any deviation to eliminate any shackles of the language of the source text. Hence, the translated literary work is as close as possible to the characteristics of target readers. Creativity refers to any subjective performance of translator’s artistic scheme fulfilling his or her subjective intention. This article attempts to analyze the translation of William Butler Yeats’-an Irish poet who has won 1946 Nobel Prize in Literature- poem: